Relationship Between Urid Acid Levels With Fasting Blood Sugar - Sitorus, Cindy Veronica; Simbolon, Demsa; Kamsiah, Kamsiah (Jurnal Kesehatan Prima, 2025)
Introduction: Uric acid the end product of purine catabolism in the human body. The cause of increased uric acid levels is influenced by various factors including alcohol, genetics, hypothyroidism, obesity, and a diet high in purines. Diabetes is a chronic metabolic disease characterized by increased blood sugar, which is caused by an imbalance between blood supply and the need to increase glucose into cells to make it available for cell metabolism and growth. The decrease or absence of insulin makes glucose stuck in the blood and causes blood sugar to increase, while cells lack glucose which is needed for cell survival and function. Objective: To determine the relationship between blood uric acid and fasting blood sugar levels in the Academic Community of the Bengkulu Ministry of Health Polytechnic. Methods: The design of this study was observational with a cross sectional design. This research was conducted on May 8-19, 2023. Sampling in this research will be conducted at the Bengkulu Ministry of Health Polytechnic. Data collection techniques use secondary data. The data collected was then processed and analyzed using Univariate analysis to find out the average frequency distribution of each variable and a data normality test was performed between uric acid levels and fasting blood sugar levels, and bivariate analysis using the Pearson correlation test. Results: There was no significant relationship between uric acid levels and fasting blood sugar levels in the Academic Community of the Bengkulu Ministry of Health Polytechnic in 2022 (p=-0.051). There is no relationship between uric acid levels in men and women with fasting blood sugar levels of the Academic Community at the Bengkulu Ministry of Health Polytechnic in 2022 (p=0.872) and (p=0.470). Conclusion: There is no significant relationship between uric acid levels and fasting blood sugar levels in the Academic Community of the Bengkulu Ministry of Health Poltekkes in 2022.